Realistic Mathematics Education Improves Trigonometric Ratios: A Classroom Action Research Study - Hazim Saputra Filia Reza; Amelia Defrianti Putri; Dhanachat Anuniwat (SJME (Supremum Journal of Mathematics Education), 2026)
This study aims to improve mathematics learning outcomes of Grade X Phase E.2 students at SMA Negeri 13 Padang through the implementation of the Realistic Mathematics Education (RME) approach. The research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The study was conducted in two learning cycles designed continuously to enhance the quality of the teaching and learning process. Data were collected through essay-type tests in trigonometric ratios to measure students’ learning outcomes and observation sheets to assess students’ learning activities and engagement during classroom instruction. The results indicate a significant improvement in students’ average scores in trigonometric ratios, increasing from 76.67 in Cycle I to 96.86 in Cycle II, representing a gain of 20.19 points. Based on the analysis of test results and observational data, students showed better conceptual understanding, higher participation, and improved ability to connect mathematical concepts with real-life contexts. These findings demonstrate that the RME approach is effective in enhancing students’ mathematics achievement and overall learning quality at the secondary school level.